“The patient was admitted…, operated… and recovered quickly…” – a narrative study of medical events in the abstract section of English case reports from otolaryngology - Zabielska, Magdalena (Focus on events and narratives in language, psychology, social and medical practice, 2020)
This article constitutes a study of the narrative included in the abstract section in case reports from a professional medical journal from otolaryngology. The rationale behind this analysis is that the abstract section is seen not only as the essence of a publication but also as a story in which sequences of events are presented. These events constitute part and parcel of a particular medical practice of case reporting, following thus specific ordering and modes of content presentation, i.e. of the patient, the disease and of the treatment process. This way they yield themselves to narrative analysis. The objective of the paper is to determine the narrative properties of their characteristic discourse.